Prakerin dan Hasil Belajar Mata Pelajaran Produktif Terhadap Kesiapan Kerja Siswa - Suciani, Nining; Panggayuh, Vertika (JoEMS (Journal of Education and Management Studies), 2025)
Education plays an important role in improving the quality of human resources, one of which is through Vocational High Schools (SMK) that aim to prepare graduates to be professionally ready to work. However, the high unemployment rate among SMK graduates shows that students' work readiness still needs to be improved. One factor that influences work readiness is the experience of Industrial Work Practice (Prakerin) and learning outcomes in productive subjects. Prakerin provides students with the opportunity to gain real-world work experience, while productive subjects equip students with knowledge and skills relevant to their field of expertise. This study aims to analyze the influence of Prakerin and learning outcomes on the work readiness of 12th grade students at SMK Islam Sunan Kalijaga, both partially and simultaneously. The results of this study are expected to contribute to the development of theoretical studies on student work readiness and provide practical input for schools and policy makers in designing effective learning strategies and implementing Prakerin, in order to produce competent and competitive graduates in the world of work.